28 MHz swept source at 1.0 μm for ultrafast quantitative phase imaging - Wei, Xiaoming (Biomed Opt Express, 2015)
Emerging high-throughput optical imaging modalities, in particular those providing phase information, necessitate a demanding speed regime (e.g. megahertz sweep rate) for those conventional swept sources; while an effective solution is yet to be demonstrated. We demonstrate a stable breathing laser as inertia-free swept source (BLISS) operating at a wavelength sweep rate of 28 MHz, particularly for the ultrafast interferometric imaging modality at 1.0 μm. Leveraging a tunable dispersion compensation element inside the laser cavity, the wavelength sweep range of BLISS can be tuned from ~10 nm to ~63 nm. It exhibits a good intensity stability, which is quantified by the ratio of standard deviation to the mean of the pulse intensity, i.e. 1.6%. Its excellent wavelength repeatability, <0.05% per sweep, enables the single-shot imaging at an ultrafast line-scan rate without averaging. To showcase its potential applications, it is applied to the ultrafast (28-MHz line-scan rate) interferometric time-stretch (iTS) microscope to provide quantitative morphological information on a biological specimen at a lateral resolution of 1.2 μm. This fiber-based inertia-free swept source is demonstrated to be robust and broadband, and can be applied to other established imaging modalities, such as optical coherence tomography (OCT), of which an axial resolution better than 12 μm can be achieved.